The Prevalence of Beers Criteria Medication Use and Associations with Falls in Geriatric Patients at a Level 1 Trauma Center. Issue 8 (August 2019) - Walker, Benjamin S.; Collier, Bryan R.; Bower, Katie L.; Lollar, Daniel I.; Faulks, Emily R.; Matos, Miguel; Nussbaum, Michael S.; Hamill, Mark E.
The Beers Criteria for Potentially Inappropriate Medication (PIM) use is a list of medications with multiple risks in older patients. Approximately 24 per cent use rate is reported in prior studies. Our objective was to determine the local PIM use and subsequent fall risk in geriatric trauma patients. We conducted a retrospective analysis of PIM use in all geriatric patients evaluated at our Level 1 trauma center between 2014 and 2017. Patients were identified from our trauma database. Pre-admission medication use was determined through medication reconciliation from our electronic medical record (EMR). Patients not undergoing medication reconciliation were excluded. After initial analysis, patients were stratified by age into three groups: 65 to 74, 75 to 84, and ≥85 years. Multivariate logistic regression analyses were used to calculate odds ratios of falls for specific PIMs. In all, 2181 patients met the inclusion criteria. Overall, 71.2 per cent of geriatric trauma patients were prescribed at least one PIM—73.1 per cent of falls compared with 68.6 per cent for other mechanisms. Specific PIM use varied by age group. PIMs associated with fall risk in all patients included antipsychotics, benzodiazepines, and diclofenac. For those aged 65 to 74 years, antihistamines, diclofenac, proton pump inhibitors, and promethazine were associated. In those aged 75 to 84 years, alprazolam, antipsychotics, benzodiazepines, cyclobenzaprine, diclofenac, and muscle relaxants were implicated. No significant associations were found for patients aged ≥85 years. PIM use at our trauma center seems to be rampant and well above the national average. Geriatric falls were associated with using ≥1 PIM and multiple specific PIMs implicated. We are designing a targeted educational program for local primary care physicians (PCPs) that will attempt to decrease geriatric PIM use.